(Non-) Essential knowledge for (new) architecture - Hays, David Lyle. (306090, 2013)
(Non-) essential knowledge for (new) architecture / David L. Hays -- Prognostication : On futurology and architecture: from Vorhersage to Vorausschau / Ludwig Engel and Johannes Gabriel ; The essential Seagram / McLain Clutter ; Savior city / Ellen Hartman -- Reversal : Contextual transformations: the landscape archived> the archive landscape / Gisli Pálsson and Miriam Kelly ; Feral bestiary / Catherine Seavitt Nordenson -- Historical space : What about SPACE? / Eeva-Liisa Pelkonen ; House, globe, dome / Jonathan Massey -- Mathematics and form : Form logics: mathematical models and design knowledge / Andrew Witt ; Other projections / Mark Ericson ; Transformations / Robert J. Krawczyk -- Profession : Constructing communication / Irene Hwang ; The future [crossed out] architect / Simone Ferracina -- Visualization : Cinematic-aided design and architecture: sources, methods, and potentials / Amir Soltani ; Data and formulaic expression of dreams, and a day in the life of the mindscaper / Chris Teeter --Thought experiment : Competitions are dead, welcome to proposals / Eduard Sancho Pou ; Architecture and fiction / Nora Wendl -- Empathy : Cold case cathedrals / Jimmy Stamp ; Architecture & trapping / Hermione Spriggs and Greg W. Barton.